Enobosarm (GTx-024, S-22): a potential treatment for cachexia. (February 2014) - Srinath, Reshmi; Dobs, Adrian
ABSTRACT  Muscle loss and wasting occurs with aging and in multiple disease states including cancer, heart failure, chronic obstructive pulmonary disease, end-stage liver disease, end-stage renal disease and HIV. Cachexia is defined as a multifactorial syndrome that is associated with anorexia, weight loss and increased catabolism, with increased morbidity and mortality. Currently no therapy is approved for the treatment or prevention of cachexia. Different treatment options have been suggested but many have proven to be ineffective or associated with adverse events. Nonsteroidal selective androgen receptor modulators (SARMs) are a new class of anabolic agents that bind the androgen receptor and exhibit tissue selectivity. Enobosarm (GTx-024, S-22) is a recently developed SARM, developed by GTx, Inc. (TN, USA), which has been tested in Phase I, II and III trials with promising results in terms of improving lean body mass and measurements of physical function and power. Enobosarm has received fast track designation by the US FDA and results from the Phase III trials POWER1 and POWER2 will help determine approval for use in the prevention and treatment of muscle wasting in patients with non-small-cell lung cancer. This article provides an introduction to enobosarm as a new therapeutic strategy for the prevention and treatment of cachexia. A review of the literature was performed using search terms 'cachexia', 'sarcopenia', 'SARM', 'enobosarm' and 'GTx-024' in September 2013 using multiple databases as well as online resources.